Hypersensitive Response of Plasmid-Encoded AHL Synthase Gene to Lifestyle and Nutrient by Ensifer adhaerens X097 - Zeng, Yanhua; Wang, Yanli; Yu, Zhiliang; Huang, Yili (Frontiers in Microbiology, 2017)
It is known that some bacteria, especially members of the family Rhizobiaceae, have multiple N-acyl homoserine lactones (AHL) synthase genes and produce multiple AHL signals. However, how bacteria selectively utilize these multiple genes and signals to cope with changing environments is poorly understood. Ensifer adhaerens is an important microorganism in terms of biotechnology, ecology and evolutionary. In this study, we investigated the AHL-based QS system of Ensifer adhaerens X097 and its response to different lifestyles or nutrients. Draft genome sequence data indicated that X097 harbored three distinct AHL synthase genes (ensI1, 2, 3) and seven luxR homologs, which was different from other E. adhaerens strains. In vitro expression indicated that plasmid-encoded ensI1 and ensI2 directed production of multiple AHLs, while chromosome-encoded ensI3 only directed production of C14-HSL. Predicted three dimensional structure of EnsI3 was quite different from that of EnsI1 and EnsI2. X097 produced different AHL profiles in LB and NFB medium, under biofilm and planktonic lifestyle, respectively. Notably, expression of ensI1 and ensI2 but not ensI3 is hypersensitive to different lifestyles and nutrients. The hypersensitive response of plasmid-encoded AHL synthase genes to different culture conditions may shed a light on the phylogenetic development of AHL synthase genes in Rhizobiaceae family.